Convergence and Divergence: Strategies for Proving Digital Evidence in Common Law and Indonesian Law Systems - Rommy Hardyansah; Rio Saputra (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This literature study conducts a normative comparative analysis of digital evidence adduction strategies in Indonesian civil law and United States common law systems. The research examines the legal construction of authentication, integrity assessment, and the strategic challenges and opportunities in utilizing various digital evidence types, such as chats, emails, CCTV footage, blockchain data, and metadata. Using a qualitative library research method with content and comparative analysis, the study finds that Indonesia's approach is codification-based, placing the judge as an active seeker of material truth who evaluates digital evidence against formal and material requirements stipulated in the Electronic Information and Transactions Law and its implementing regulations. In contrast, the U.S. common law system employs a rigorous adversarial strategy, where digital evidence is tested through extensive discovery and cross-examination, with the judge acting as a procedural gatekeeper under the Federal Rules of Evidence. The core difference lies in the locus of substantive evaluation: Indonesian judges assess probative value directly, while common law juries do so after judicial admissibility screening. The study concludes that both systems are converging on the necessity of technical expertise but recommends that Indonesia enhance judicial digital literacy and consider limited e-discovery mechanisms to strengthen its evidentiary framework.